Study of different social rewards used in Down's syndrome children's early stimulation - Sanz, Teresa; Menéndez, Javier; Rosique, Teresa (Early child development and care, 2011)
This article describes the results obtained with two types of social rewards used in early stimulation of Down's syndrome children. In the study we focus on the efficiency of the employment of the social rewards or reinforcements used in the early stimulation, bearing in mind that the children with Down's syndrome possess a social development quotient over our intellectual level. We worked with 20 Down's syndrome children of the age from five months up to two years and used two types of social reinforcements. All the subjects received stimulation in the areas of gross motor, fine motor, language and social skills. The findings indicate that better results are achieved if we give verbal approval together with some agreeable gesture (e.g. as plaudits) before the correct executions.